Who Acquires Friends Through Social Media and Why? “Rich Get Richer” Versus “Seek and Ye Shall Find” - Tufekci, Zeynep (Proceedings of the International AAAI Conference on Web and Social Media, 2010)
There is an ongoing debate, not just among academics but in popular culture, about whether social media can expand people’s social networks, and whether online friends can be “real” friends. The debate refuses to die. This paper addresses this question subjectively, from the point of view of the user, and examines the predictors of acquiring new friends through social media use. This is a multi-method study with quantitative (n=617) and qualitative sections. Some previous studies have found a “rich-get-richer” effect where people who are socially active offline appear to benefit most from online interactions. This paper is based on the idea that whether online friends can be real friends may be subject to a self-fulfilling prophecy: those who do not believe that online friendships can be real friendships are not likely to make such connections. I compare the “Rich Get Richer” and “Seek and Ye Shall Find” models by examining relationships between the amount of offline socializing, amount of online social activity and the belief in online friendships. I also qualitatively examine reasons cited by respondents as to why online sociality is or is not a plausible route to meaningful friendship. The results show strong support for one of the earliest theories of computer-mediated-communication: hyperpersonal interaction. It appears that a sizable portion of the young generation finds online interaction positive because it is perceived to concentrate on the conversation itself, rather than on appearances, and is seen as freer of social judgments. African-Americans are significantly more likely to meet new friends online. There also appear to be underlying personality traits, apart from traditional demographic variables, that divide the population in terms of their attitude towards online sociality.